Avaliação de metais em material particulado MP10 na fronteira Brasil-Paraguai (Ponte da Amizade) - Aikes, Matias Alfredo (2019)
Atmospheric pollution has intensified over the years, along with-it particulate matter is a major conditioner of this pollution, emitted by natural and anthropogenic sources. In urban environments, vehicle traffic is a major contributor to its emission. There is a wide range of problems related to exposure to atmospheric pollutants, both for human health (respiratory and cardiovascular diseases) and the environment (causing changes in plant morphology, biochemical parameters and physiological aspects). The aim of this study was to characterize the metallic species present in atmospheric particulate matter at the Brazil and Paraguay border, in Foz do Iguacu city - Paraná. The atmospheric concentrations of Fe, Al, Ca, K, Na, Mg, Zn, Cr, Cu, Pb, Mn and Cd elements in the MP10 fraction were determined in acidified filter extracts using ICP-OES techniques. Samples were collected in two distinct periods, summer, usually humid, and winter, predominantly dry, using a large volume sampler (Hi-vol). The results showed that the study region has the PM composition strongly linked to natural sources but is directly influenced by anthropic sources. The concentration of the elements varied according to the sampling period. In winter there was a higher presence of metals, except for Ca, Pb and Na. Finally, analyzing the air mass trajectories, noted that certain particulate material components may come from other locations to the study region.